Aspects of power sensitivity among social workers and social work students: a comparative study - Melanie Misamer; Claudia Bartels; Michael Belz (Frontiers in Medicine)
The asymmetrical nature of the relationship between social workers and their clients may lead to abuse of power due to a human trait or corruption. A high level of power sensitivity is thus crucial to counteract power abuse. Ideally, this topic should be covered during studies, as the risk of corruption rises with everyday working life. In this study, we aimed to assess basic and specific aspects of power sensitivity both for 271 students and 414 professionals, covering (1) general differences for the total sample, (2) differences between both groups and (3) differences between subgroups (semesters, professional years, field of profession; ratings from 0 to 100%). While importance of power sensitivity (94.7%) and professional ethics/principles (91.9%) were rated higher than all other items (p < 0.001), a stark difference was found between the participants’ own vs. the anticipated professional groups’ power sensitivity (73.9% vs. 53.4%, p < 0.001). A hypothetical individual change for the worse through the power as social worker was rated significantly lower than all other items on the respective scale (61.5%, p < 0.001). Professionals rated the experience of stereotypical ideas and prejudices towards clients (78.5, 75.2%) to be significantly stronger than students (69.4, 67.4% all p < 0.001). For students, power sensitivity generally increased with semesters (p < 0.001), while it remained stable over professional years for social workers. Differences between fields of profession did not reach significance. In summary, both students and professionals emphasized the importance of power sensitivity, but seemed to show a self-serving bias if they compared themselves to their group – considering a possible corruption effect, this may at least be interpreted as problematic. We discuss room for improvement in terms of sensitization, whether in the context of further training (professionals) or curricula (students).